Effects of Roselle extract and Magic Grow Tonic Balanced Solution spray on Vegetative Growth and Flowering of Tagetes erecta - Al-Meziraa, Hajer Sattar; Al-Jubouri, Fatima Fajer; El-Shouely, Mohammed Hassan. (Journal of agricultural, environmental and veterinary sciences, 2021)
A field experiment was conducted in Basra city during 2020-2021 to assess the effect of three levels of Roselle extract (Hibiscus subdaiffa L.) at 0.3 and 5.7 g.L-1 and three levels of balanced solution Magic Grow Tonic (0, 3, 5, 7 m.L-1) and their interaction. The experiment was factorial experiment in Randomized Complete Block Design (R.C.B.D) with three replications. Results showed that spraying with the Roselle extract and balanced solution interaction at 5g. L-1 Roselle extract + 7 ml. L-1 Magic Grow Tonic give the highest rate plant height 30.87) cm) leaves number 16.44) leaf. plant-1) flower number 11.95) flower. Plant-1), flower diameter 5.86) cm) except the stem diameter surpassed as sprayed with 5g.L-1 Roselle extract + 5ml.L-1 Magic Grow Tonic 7.88) mm), while the spray with 3g.L-1 Roselle extract + 7ml.L-1 Magic Grow Tonic superior in the dry matter in leaf and flower stem of flowers (17.48%), (%18.43) and 3.51) cm). the treatment of balanced solution at a concentration of )7.5ml.L-1( gave highest dray Wight for plant 58.72) g).